2013
DOI: 10.1016/j.neuroscience.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics uncovers dietary omega-3 fatty acid-derived metabolites implicated in anti-nociceptive responses after experimental spinal cord injury

Abstract: Chronic neuropathic pain is a frequent comorbidity following spinal cord injury (SCI) and often fails to respond to conventional pain management strategies. Preventive administration of docosahexaenoic acid (DHA) or consumption of a diet rich in omega-3 polyunsaturated fatty acids (O3PUFAs) confers potent prophylaxis against SCI and improves functional recovery. The present study examines whether this novel dietary strategy provides significant antinociceptive benefits in rats experiencing SCI-induced pain. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 102 publications
3
67
0
Order By: Relevance
“…119,120 Furthermore, some current dry eye treatments, such as omega 3 and doxycycline (an MMP inhibitor), likely have a direct effect on nerve function along with secondary effects by improving the ocular surface environment. [121][122][123] Further studies are needed to assess whether topical and/or centrally acting neuromodulators have a role in the treatment of dry eye patients with features of NOP.…”
Section: Neuropathic Ocular Pain and Implications For Dry Eye Treatmentmentioning
confidence: 99%
“…119,120 Furthermore, some current dry eye treatments, such as omega 3 and doxycycline (an MMP inhibitor), likely have a direct effect on nerve function along with secondary effects by improving the ocular surface environment. [121][122][123] Further studies are needed to assess whether topical and/or centrally acting neuromodulators have a role in the treatment of dry eye patients with features of NOP.…”
Section: Neuropathic Ocular Pain and Implications For Dry Eye Treatmentmentioning
confidence: 99%
“…PUFAs are involved in many physiological functions, including brain and retinal development, aging, memory, synaptic membrane function, photoreceptor function, and neuroprotection (Bazan, 2003(Bazan, , 2006Eady et al, 2014;Hong et al, 2014). Recently, PUFAs such as DHA have been reported to interact with some pain conditions (Figueroa et al, 2013;Torres-Guzman et al, 2014). We recently reported that DHA and/or GW9508, a GPR40 agonist, have suppressive effects on pain behavior elicited by formalin, acetic acid and a complete Freund's adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, it has been demonstrated that treatment of pain (it is calculated some 40-60% sufferers) in Alzheimer's patients (unable to report it) minimizes serious behavioral and psychological symptoms (agitation, aggression, etc) [15]. Incidentally, it has been reported that DHA reduces experimentally induced chronic pain [16].…”
Section: Journal Of Anesthesia and Intensive Care Medicinementioning
confidence: 99%